PROBLEMATIKA PERIZINAN DEPOT AIR MINUM DI KOTA PEKANBARU TAHUN 2013 - Resti Nelly; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was aimed to analtzed problematies of licensing drinking water refill indutries and stakeholders that related in Pekanbaru 2013. This study was an abalysis descriptive and used primary and secondary data. Primary data based on questionnare and interviwed indrustrialist of drinking water refill and stakeholders that related for giving licensing in drinking water refill industries. Secondary data based on recommandation latter from Health Department of Pekanbaru, Registered latter fromIndustry and Trade Departement of Pekanbaru, and Disarder letter from Integrated Service and Investment Departement of Pekanbaru, according to minister of Industry and Trade of RI, numb 651/Kep/2004 about rules and regulation and trading of drinking water refill industries. The study showed that in 2013, only 149 industries that have recommandation letter from Health Departement, 54 Industries that have registered letter from Industry and Trade and Investment Departement of Pekanbaru. It was showed that only drinking water refill industries had registered legally. In order to reach a good condition, there must be a good communication between goverment and drinking water refill industries and also goverment have to socialize the importance of licensing for drinking water refill industries. Goverment also have to give firm punishhment for whoever that breaks the rules and regulation.Keywords : Drinking Water Refill Industries Licensing, Problematics, Registering